Experimental Investigation and Image Processing to Predict the Properties of Concrete with the Addition of Nano Silica and Rice Husk Ash - Saavedra-Flores, E; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The use of the combination of ultrafine rice husk ash (RHA) and nano silica (NS) enhances the compactness of hardened concrete, but there is still a lack of studies that address the effects of NS and RHA on the workability, mechanical properties and pore microstructure of concrete. This study mainly aims to investigate the influence of the pore size distribution in multiphysics concrete model modified by NS and RHA and to determine the workability and mechanical properties of concrete with NS and RHA. In this work, NS and RHA were used as 0, 5, 10, 15 and 20% replacements of ordinary Portland cement (OPC) in concrete grade M20. Concrete mixed with NS and RHA showed improved performance for up to 10% addition of NS and RHA. Further addition of NS and RHA showed a decrease in performance at 7, 14 and 28 days. The decrease in concrete porosity was also found to be up to 10% when adding NS and RHA to cement. Image processing was performed on the cement-based materials to describe the microstructure of the targeted material without damage. The results from the experimental and tomography images were utilized to investigate the concrete microstructure and predict its inner properties. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: image processing; nano silica; rice husk ash; pore microstructure; multiphysics concrete model; properties